Leakage-aware scheduling for embedded real-time systems with (m, k)-constraints. (1st January 2013) - Niu, Linwei; Quan, Gang
In this paper, we study the problem of reducing both the dynamic and leakage energy consumption for real-time systems with ( m, k )-constraints, which require that at least m out of any k consecutive jobs of a task meet their deadlines. Two energy efficient scheduling approaches incorporating both dynamic voltage scheduling (DVS) and dynamic power down (DPD) are proposed in this paper. The first one statically determines the mandatory jobs that need to meet their deadlines in order to satisfy the ( m, k )-constraints, and the second one does so dynamically. The simulation results reveal that, with more accurate workload estimation, our proposed techniques outperformed previous research in both overall and idle energy reduction while providing the ( m, k )-guarantee.